Studi Pemilihan Alternatif Perkuatan Timbunan Badan Jalan di Atas Tanah Lunak dengan Metode Elemen Hingga dan Sistem Pengambilan Keputusan - Prayitno, Deo Pratama; Purwanto, Edy (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2025)
Toll road construction often encounters geotechnical challenges due to soft soil conditions, which can significantly affect embankment stability, as observed on the Balikpapan–Samarinda Toll Road at STA 22+300, NSPT value is ≤ 6 up to a depth of 10 metres. This study aims to analyse the stability of the road embankment and determine an effective and efficient soil reinforcement solution. Slope stability analysis was performed using the finite element method with Plaxis 2D, while decision-making employed the pairwise comparison and simple additive weighting methods. The existing condition analysis revealed a factor of safety of 0.9852 and a settlement of 32.02 cm. The combination of mini piles and geotextiles demonstrated the best performance, increasing the factor of safety to 1.552 and reducing settlement to 13.03 cm. With the highest decision-making preference weight of 0.8989, this alternative was identified as the optimal solution, offering adequate stability, relatively low settlement, and cost efficiency compared to the spun pile–geotextile combination.